Digital Learning Media Assisted by Quizizz Application (METALIQ) on Science Content of Ecosystem Topic for Sixth Grade Elementary School - Astafiria, Nanda Sekar; Bayu, Gede Wira (Universitas Pendidikan Ganesha, 2021)
Distance learning requires learning activities that focus on the use of technology, so we need a digital learning media that not only functions as an evaluation tool, but can also convey learning materials. This study aims to produce â€œMETALIQâ€ which was developed on the topic of Ecosystems for the sixth-grade elementary school students. This research was a development research based on the ADDIE model procedure. The subject of this research was